1985
DOI: 10.1128/jb.162.3.918-924.1985
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane permeability channels across the outer membrane of Haemophilus influenzae type b

Abstract: Outer membranes of Haemophilus influenzae type b were fractionated to yield Triton X-100-insoluble material and lipopolysaccharide and phospholipids. Liposomes reconstituted from lipopolysaccharide and phospholipids were impermeable to sucrose (Mr, 342) and to a high-molecular-weight dextran (average Mr, 6,600). When the Triton X-100-insoluble material was introduced into the reconstituted liposomes, the vesicles became permeable to sucrose, raffinose (Mr, 504), and stachyose (Mr, 666) and fully retained dextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Differences in the size of the porin channels appear to account for some of the differences observed in the minimum inhibitory concentrations of various gramnegative bacteria. For example, Huemophilus influenzae is thought to be much more susceptible to p-lactam antibiotics than E. coli due to the presence of larger porin channels (44). Specific mutations of gene(s) coding for the porin proteins can further impair the entry of hydrophobic penicillins into the cell and result in an increase in the minimum inhibitory concentration of the antibiotic for the organism.…”
Section: Resistance To Tetracycline Antibioticsmentioning
confidence: 99%
“…Differences in the size of the porin channels appear to account for some of the differences observed in the minimum inhibitory concentrations of various gramnegative bacteria. For example, Huemophilus influenzae is thought to be much more susceptible to p-lactam antibiotics than E. coli due to the presence of larger porin channels (44). Specific mutations of gene(s) coding for the porin proteins can further impair the entry of hydrophobic penicillins into the cell and result in an increase in the minimum inhibitory concentration of the antibiotic for the organism.…”
Section: Resistance To Tetracycline Antibioticsmentioning
confidence: 99%
“…The purification scheme for porin of Hib strain ATCC9795 as described by Vachon et at. (1985) yielded a single species of protein when stained with Coomassie Brilliant Blue.…”
Section: Monoclonal Antibodies Against Hib Porinmentioning
confidence: 99%
“…We have studied the Hib porin extensively and have shown that it has a molecular mass exclusion limit to solutes greater than 1400Da (Vachon et at., 1985). a cross-sectional diameter of 0.9 nm (as determined by reconstitution into black lipid membranes; Vachon etai, 1986), and a trimeric organization in the outer membrane (Vachon et at.. 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstituted outer membranes of gram-negative bacteria for example have exclusion limits to passive diffusion that range between 600 and 3000 g mol-'. [33][34][35] This suggests that only oligomeric tannins can effectively penetrate bacteria. Penetration is also an important factor involved in the interactions of tannins with complex proteins.…”
Section: Detoxification Of Bark Tanninsmentioning
confidence: 99%